2019
DOI: 10.1155/2019/2679791
|View full text |Cite
|
Sign up to set email alerts
|

Using the RISK-PCI Score in the Long-Term Prediction of Major Adverse Cardiovascular Events and Mortality after Primary Percutaneous Coronary Intervention

Abstract: Background/Aim The RISK-PCI is a simple score for the prediction of 30-day major adverse cardiovascular events (MACE) and mortality in patients treated with primary PCI (pPCI). The aim of the present study is to evaluate the prognostic performance of the RISK-PCI score in predicting MACE and mortality in the long-term follow-up of STEMI patients treated with pPCI. Method The present study enrolled 2,096 STEMI patients treated with pPCI included in the RISK-PCI trial. Patients presenting with cardiogenic shock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Two patients had a myocardial infarction (MI), nine patients had heart failure, one patient had a stroke, and two patients died of cardiovascular causes during longterm follow-up. The discrimination of the RISK-PCI score to predict 1year MACE and death was pretty strong, as was shown in a previous research by [24], which corroborated our findings. The 1-year MACE c-statistics was 0.78 (95% CI 0.73-0.79, p 0.001), the 6-year MACE c-statistics was 0.75 (95% CI 0.68-0.75, p 0.001), the 1-year mortality cstatistics was 0.87 (95% CI 0.84-0.89, p 0.001), and the 6year mortality c-statistics was 0.83 (95% CI 0.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Two patients had a myocardial infarction (MI), nine patients had heart failure, one patient had a stroke, and two patients died of cardiovascular causes during longterm follow-up. The discrimination of the RISK-PCI score to predict 1year MACE and death was pretty strong, as was shown in a previous research by [24], which corroborated our findings. The 1-year MACE c-statistics was 0.78 (95% CI 0.73-0.79, p 0.001), the 6-year MACE c-statistics was 0.75 (95% CI 0.68-0.75, p 0.001), the 1-year mortality cstatistics was 0.87 (95% CI 0.84-0.89, p 0.001), and the 6year mortality c-statistics was 0.83 (95% CI 0.…”
Section: Discussionsupporting
confidence: 92%
“…There was no statistically significant difference between the two groups in terms of RISK-PCI score, despite the fact that the mean score was greater for patients who had MACE and mortality during in-hospital follow-up compared to those in the Long term group. In a recent study [24] showed that, the RISK-PCI score remained an independent predictor for 1-year MACE (HR 1.24, 95% CI 1.18-1.31, p < 0.001), 6-year MACE (HR 1.22, 95% CI 1.16-1.28, p < 0.001), 1-year mortality (HR 1.21, 95% CI 1.13-1.29, p < 0.001), and 6-year mortality (HR 1.23, 95% CI 1.15-1.31, p < 0.001). Risk-PCI was significantly correlated with major adverse cardiac events (MACE), including death both during and after hospitalisation.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous studies have reported that the incidence of MACE is 10.9-30.5% if there is no related treatment among patients receiving PCI (23)(24)(25). Several therapies are recommended to prevent the incidence of MACE during the perioperative period of PCI according to the American College of Cardiology/AHA guidelines, among which statins serve a crucial role (26,27).…”
Section: Discussionmentioning
confidence: 99%